Aetiologies of Acute Undifferentiated Febrile illness in Adult Patients – an Experience from a Tertiary Care Hospital in Northern India - Mittal, Garima (J Clin Diagn Res, 2015)
INTRODUCTION: Acute undifferentiated febrile illness (AUFI) is a common clinical entity in most of the hospitals. The fever can be potentially fatal if the aetiology is not recognized and appropriately treated early. AIM: To describe the aetiology of fever among patients in a tertiary care hospital in Northern India. MATERIALS AND METHODS: A one-year retro-prospective, observational study was conducted in adults (age>18years) presenting with undifferentiated febrile illness (of duration 5-14 days). Diagnosis was confirmed by suitable laboratory tests after exhaustive clinical examination. RESULTS: A total of 2547 patients with AUFI were evaluated. Of these, 1663 (65.3%) were males and 884 (34.7%) were females. Dengue (37.54%); enteric fever (16.5%); scrub typhus (14.42%); bacterial sepsis (10.3%); malaria (6.8%); hepatitis A (1.9%); hepatitis E (1.4%); leptospirosis (0.14%); were the main infections while no specific diagnosis could be delineated in 11%. Mixed infections were noted in 48 (1.9%) patients. CONCLUSION: A good clinical acumen supported by the basic investigations can help diagnose the cause of fever with reasonable certainty.